The Role of Organizational Culture in Moderating Budget Performance Determinants - Wulandari, Retno Asih; Khafid, Muhammad; Sri Wahyuningrum, Indah Fajarini (Universitas Negeri Semarang, 2021)
This research was conducted to identity the influence ofquality of human resources, the quality of budgeting and the quality of the internal control system has a direct effect on budget performance. In addition, this research was conducted to identity the influence of moderating variables of organizational culture on the relationship between quality of human resources, the quality of budgeting and the quality of the internal control systemhas a effectbudget performance. The design research of this research uses a quantitative approach. The sample in this study were 31 work units at both the faculty and postgraduate levels of the State University in Semarang City. Data analysis used descriptive analysis and inferential analysis using Moderated Regression Analysis (MRA) with application program SPSS. The results of this study indicate that the quality of human resources, the quality of budgeting and the quality of the internal control system has a direct effect on budget performance. The organizational culture as a moderating variable is proven to moderate the influence of quality, the budgeting quality, and the internal control system quality on budget performance.